Studying the interstellar medium to look for relics of triggered star formation among stellar clusters - Paron, Sergio Ariel (2021)
Evidence of triggered star formation at large spatial scales involving stellar clusters is scarce. We investigate a Galactic region (l = 130°.0, b = 0°.35) populated by several open stellar clusters that according to the last Gaia data release, are located at a distance of about 2.9 kpc. By analysing the interstellar medium (ISM) at infrared, centimeter, and millimeter wavelengths towards this group of clusters we discovered a shell of material of about 2° in size at the same distance. We suggest that the shell, mainly observed at 12 μm and in the H i emission at 21 cm, was generated by the action of massive stars belonging to clusters Berkeley 7 and UBC 414, which lie at its centre. Five clusters (MWSC0152, Czernik 6, Czernik 7, Berkeley 6, NGC 663, and NGC 654) lie at the border of this shell. From the comparison between the dynamical time of the discovered H i shell and the analysis of the ages of stellar populations in these clusters, we conclude that the expansion of the shell could have triggered in the past the formation of stars in some of them. We point out that in order to find physical evidence supporting a genetic connection between stellar clusters, it is necessary not only to study the individual clusters and their stellar populations, but also to investigate their surrounding ISM at a large spatial scale.